Foster productive conversation around gun control on campus. Issue 12 (April 2017) - Sutton, Halley
Abstract : SAN FRANCISCO — With more states nationwide allowing concealed carry of firearms on campuses and the ensuing controversy on both sides, how do you foster productive communication that ensures well‐being for all? Promoting well‐being on campus starts with being able to discuss issues safely and constructively even when people on different sides of the issue feel strongly. In a session at the Association of American Colleges and Universities annual meeting, Jonathan Metzl, director of the center for medicine, health, and society at Vanderbilt University, shared strategies for facilitating productive conversations about guns on campus. "Whether or not you want it, it [the issue of gun control] is coming to your campus, " Metzl said. Be prepared for talking through differing viewpoints on campus.